The United Nations preventing human trafficking - Dufková, Šárka; Lehmannová, Zuzana, 1951-; Sršeň, Radim; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
Human trafficking is a type of modern day slavery, yearly it affects millions of people worldwide and yet it is rather overlooked by governments and general public. Human trafficking for the purpose of sexual exploitation is its most common form. United Nations is the biggest organizations combating this issue. This thesis attempts to evaluate the role of United Nations in combating human trafficking. For the purpose of this thesis were used three methods; description, induction and comparative analysis. First part focuses on United Nations, its organization and measures which are set in order to combat given issue. Second part describes case study of two regions, Europe and Southeast Asia. It was concluded that United Nations have all necessary tools to significantly influence improvement of the phenomenon human trafficking, however up till today it has not fulfilled its true potential. At the end of the thesis are added several suggestions how to improve the work of United Nations to turn this organization into a key player in combating human trafficking.
Vedoucí práce: Zuzana Lehmannová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses